Views of the Australian public on the delivery of risk-stratified cancer screening in the population: a qualitative study - Kate LA Dunlop; Nicole M Rankin; Amelia K Smit; Ainsley J Newson; Louise A Keogh; Anne E Cust (Sax Institute, 2023)
Objective and importance of study: Risk-stratified approaches to cancer screening aim to provide tailored risk advice to individuals, rather than the mostly one-size-fits-all approach designed for the average person that is currently used in Australia. Stratified cancer screening has the potential to increase the benefits and reduce the harms of screening. Initial risk assessment is a crucial first step for screening programs that use risk stratification. We report findings from a qualitative study exploring the views of the Australian public on how to best deliver risk-stratified cancer screening in the population to help inform future implementation. Study type: Qualitative interview study. Methods: We conducted semistructured interviews with participants from a previous study, half of whom had received personal genomic risk information and half of whom had not. We asked how and where they would like to see risk-stratified screening delivered and how they felt about different health professionals assessing their cancer risk. Data were analysed thematically. Results: Forty interviews were conducted. The age range of participants was 21-68 years; 58% were female. Themes included: 1) Convenience is a priority; 2) General practice is a good fit for some; 3) Web-based technology is part of the process; and 4) "I would want to know why [I was being stratified]". Similar views were expressed by both groups. Our findings suggest that although health professionals were identified as having an important role, there were mixed preferences for delivery by general practitioners, medical specialists or nurses. Participants were less concerned about who undertook the risk assessment than whether the health professional had the appropriate skill set and availability. Clear communication and evidence of the need for change in screening eligibility and frequency were key factors in the successful delivery of risk-stratified screening. Conclusion: We identified that convenience and good communication, including clear explanations to the public with convincing evidence for change, will enable the successful delivery of risk-stratified cancer screening in the population, including organised and opportunistic screening approaches. Health professional education and upskilling across disciplines will be key facilitators. Engagement and further consultation with primary care and other key stakeholders will be central.